Effect of high-dose or split-dose artesunate on parasite clearance in artemisinin-resistant falciparum malaria. - Das, D; Tripura, R; Phyo, A; Lwin, K; Tarning, J; Lee, S; Hanpithakpong, W; Stepniewska, K; Menard, D; Ringwald, P; Silamut, K; Imwong, M; et al. (2013)
BACKGROUND: The emergence of Plasmodium falciparum resistance to artemisinins on the Cambodian and Myanmar-Thai borders poses severe threats to malaria control. We investigated whether increasing or splitting the dose of the short-half-life drug artesunate improves parasite clearance in falciparum malaria in the 2 regions. METHODS: In Pailin, western Cambodia (from 2008 to 2010), and Wang Pha, northwestern Thailand (2009-2010), patients with uncomplicated falciparum malaria were randomized to oral artesunate 6 mg/kg/d as a once-daily or twice-daily dose for 7 days, or artesunate 8 mg/kg/d as a once-daily or twice-daily dose for 3 days, followed by mefloquine. Parasite clearance and recrudescence for up to 63 days of follow-up were assessed. RESULTS: A total of 159 patients were enrolled. Overall median (interquartile range [IQR]) parasitemia half-life (half-life) was 6.03 (4.89-7.28) hours in Pailin versus 3.42 (2.20-4.85) hours in Wang Pha (P = .0001). Splitting or increasing the artesunate dose did not shorten half-life in either site. Pharmacokinetic profiles of artesunate and dihydroartemisinin were similar between sites and did not correlate with half-life. Recrudescent infections occurred in 4 of 79 patients in Pailin and 5 of 80 in Wang Pha and was not different between treatment arms (P = .68). CONCLUSIONS: Increasing the artesunate treatment dose up to 8 mg/kg/d or splitting the dose does not improve parasite clearance in either artemisinin resistant or more sensitive infections with P. falciparum. Clinical Trials Registration. ISRCTN15351875.